Scattering of electromagnetic waves from dielectric microspheres - Solano-Reynoso, W. M. (2017)
The interaction of the electromagnetic ﬁeld with a homogeneous and non-magnetized isotropic dielectric sphere is described under the Mie solution of Maxwell equations, considering the absorption and scattering for a variable wavelength of electromagnetic waves with respect to the microsphere sizes.Results of the extinction factors for diﬀerent refractive indices of diﬀerent materials found in the literature and the determination of the optical thickness for spherical particles are shown.